Do maternal parenting behaviors indirectly link toddler dysregulated fear and child anxiety symptoms? - Maag, Brianne (Child Psychiatry Hum Dev, 2021)
Dysregulated fear (DF), display of high-fear in low-threat contexts, has been shown to predict child anxiety development. Maternal protective, comforting, and intrusive behaviors have also been linked to child anxiety development and may be candidate mechanisms linking DF to anxiety. First, the relation between DF (age 2) and child separation anxiety (age 4) as indirectly linked by maternal protective, comforting, and intrusive behaviors was investigated. Second, the relation between DF and social anxiety (age 4) through parenting behaviors was investigated. Results suggested DF significantly predicted child separation anxiety through maternal intrusive behaviors, above and beyond protective and comforting behaviors. Neither protective nor comforting parenting behavior served as indirect effects between DF and separation anxiety. No parenting behaviors were found to indirectly link the relation between DF and social anxiety. Results suggest that multiple parenting behaviors are involved as environmental mechanisms by which DF predicts separation anxiety.